Innate lymphoid cells and allergic inflammation - Kim, Brian S. (2013)
Group 2 innate lymphoid cells (ILC2s) play critical roles in anti-helminth immunity and airway epithelial repair. Recently, these cells have also emerged as key players in the development of allergic inflammation at multiple barrier surfaces. ILC2s arise from common lymphoid progenitors in the bone marrow, are dependent on the transcription factors RORα, GATA3 and TCF-1 and produce the type 2 cytokines IL-4, IL-5, IL-9 and/or IL-13. The epithelial cell-derived cytokines IL-25, IL-33 and TSLP regulate the activation and effector functions of ILC2s, and recent studies suggest that their responsiveness to these cytokines and other factors may depend on their tissue environment. In this review, we focus on recent advances in our understanding of how ILC2s are differentially regulated in the context of allergic inflammation and discuss the therapeutic potential of targeting ILC2s in the treatment of allergic diseases.